Transformational leadership, social capital and organizational innovation. Issue 7 (5th September 2016) - Chen, Lu; Zheng, Wei; Yang, Baiyin; Bai, Shuaijiao
Abstract : Purpose: The purpose of this paper is to investigate the forces driving organizational innovation, particularly CEO transformational leadership as it affects external and internal social capital in top management teams. Design/methodology/approach: Survey questionnaires were administered to 90 Chinese top management teams. Structural equation modeling was used to test the hypothesized relationships. Findings: Both internal and external social capital mediated the relationship between transformational leadership and organizational innovation. Practical implications: Organizations should strengthen internal and external capital of top management teams to reap maximal innovation outcomes from transformational leadership. Originality/value: The findings contribute to the transformational leadership, social capital, and innovation literature first by showing how leadership influences innovation through largely neglected mechanisms – internal and external social capital. Second, a social capital focus challenges the tacit assumption that transformational leadership has only internal influences by showing that it potentially spills over to the external domain.